2013
DOI: 10.1001/jamaophthalmol.2013.1724
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Birdshot Chorioretinopathy Using Extramacular Enhanced Depth Optical Coherence Tomography

Abstract: To combine "extramacular" and "enhanced depth" optical coherence tomographic (OCT) scanning protocols to facilitate enhanced characterization of patients with birdshot chorioretinopathy. Methods: Spectral-domain OCT images were prospectively collected from 24 eyes of 12 patients with birdshot chorioretinopathy. The images were acquired both from the macula and from 4 peripheral locations: superior and inferior to the temporal vascular arcades, nasal to the optic disc, and temporal to the macula. All images wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
65
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 46 publications
(56 reference statements)
8
65
1
1
Order By: Relevance
“…In other prior studies of BSCR, Keane et al 10 found choroidal thinning, discrete hyperreflective foci, focal depigmentation, and presence of a suprachoroidal hyporeflective space on EDI-OCT scans from 12 individuals. The authors had the impression that birdshot lesions on fundus photographs were focal areas of ''choroidal depigmentation'' suggested by increased scleral reflectivity on the OCT images.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In other prior studies of BSCR, Keane et al 10 found choroidal thinning, discrete hyperreflective foci, focal depigmentation, and presence of a suprachoroidal hyporeflective space on EDI-OCT scans from 12 individuals. The authors had the impression that birdshot lesions on fundus photographs were focal areas of ''choroidal depigmentation'' suggested by increased scleral reflectivity on the OCT images.…”
Section: Discussionmentioning
confidence: 82%
“…Using EDI-OCT, Mrejen and Spaide 9 demonstrated hyporeflective zones in the choroid of eyes with BSCR. Keane et al 10 subsequently reported choroidal depigmentation and hyperreflective foci in the choroid and speculated that these findings were most likely inflammatory in nature. Other choroidal findings by EDI-OCT included thinning of the Sattler layer, generalized choroidal thinning, focal depigmentation, and presence of a suprachoroidal space.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,42,44 In a recent study, extra-macular scans performed in eyes diagnosed with birdshot chorioretinitis demonstrated generalised choroidal thinning outside the macula. 18 Although factors including age and disease activity were well matched between the good (o0.3 LogMAR) and poor (≥0.3 LogMAR) VA groups, other confounders are possible.…”
Section: The Choroid In Granulomatous Uveitismentioning
confidence: 91%
“…[15][16][17] Several early studies have indicated how OCT-derived choroidal images can be useful in uveitic disorders. For example, OCT has been used (1) to describe characteristic features of specific uveitis entities, including thinning of Haller's large vessel layer of the choroid in idiopathic panuveitis and extra-macular choroidal changes in birdshot chorioretinopathy; 18,19 (2) to identify distinct stages of a disease process as illustrated by punctate inner choroidopathy; 20,21 (3) objective measurement of vitreous inflammation; 22 and (4) to monitor response to therapy, exemplified by a reduction of subfoveal choroidal thickening with corticosteroid therapy in Vogt-KoyanagiHarada disease. 23 Additionally, the potential of OCT angiography in uveitic diseases has yet to be realised.…”
Section: Introductionmentioning
confidence: 99%